Achievement of safer learning facilities standards in the disaster safe education unit program at Panggang elementary school - Utami, Anindita Ayu Nisa; Dwiastuti, Anggit Nur; Nurmalasari, Yuli (Universitas Negeri Yogyakarta, 2024)
This study aims to discover and describe the achievement of safer learning facility standards for the disaster safe education unit program at Panggang elementary school, Bambanglipuro. This study is a descriptive evaluative research mixed methods approach with a sequential explanatory strategy. The sampling technique was carried out with saturated samples. Data collection techniques used observation, interviews, documentation studies, and questionnaires. Data validity uses internal validation, technical triangulation, and source triangulation. Quantitative data analysis uses a percentage formula calculation according to Sugiyono, while qualitative data analysis uses an interactive analysis model. However, each aspect still has gaps. The gaps that occur are not too significant, but still affect the achievement of safer learning facilities. Efforts are needed from Panggang elementary school Bambanglipuro to reduce or even eliminate existing gaps so that safe learning facilities in the disaster safe education unit program can be fully achieved. Keywords: program evaluation, disaster safe education unit program, safer learning facilities